Molecular heterogeneity of non‐small cell lung carcinoma patient‐derived xenografts closely reflect their primary tumors. Issue 3 (7th November 2016) - Wang, Dennis; Pham, Nhu‐An; Tong, Jiefei; Sakashita, Shingo; Allo, Ghassan; Kim, Lucia; Yanagawa, Naoki; Raghavan, Vibha; Wei, Yuhong; To, Christine; Trinh, Quang M.; Starmans, Maud H.W.; et al.
Abstract : Availability of lung cancer models that closely mimic human tumors remains a significant gap in cancer research, as tumor cell lines and mouse models may not recapitulate the spectrum of lung cancer heterogeneity seen in patients. We aimed to establish a patient‐derived tumor xenograft (PDX) resource from surgically resected non‐small cell lung cancer (NSCLC). Fresh tumor tissue from surgical resection was implanted and grown in the subcutaneous pocket of non‐obese severe combined immune deficient (NOD SCID) gamma mice. Subsequent passages were in NOD SCID mice. A subset of matched patient and PDX tumors and non‐neoplastic lung tissues were profiled by whole exome sequencing, single nucleotide polymorphism (SNP) and methylation arrays, and phosphotyrosine (pY)‐proteome by mass spectrometry. The data were compared to published NSCLC datasets of NSCLC primary and cell lines. 127 stable PDXs were established from 441 lung carcinomas representing all major histological subtypes: 52 adenocarcinomas, 62 squamous cell carcinomas, one adeno‐squamous carcinoma, five sarcomatoid carcinomas, five large cell neuroendocrine carcinomas, and two small cell lung cancers. Somatic mutations, gene copy number and expression profiles, and pY‐proteome landscape of 36 PDXs showed greater similarity with patient tumors than with established cell lines. Novel somatic mutations on cancer associated genes were identified but only in PDXs, likely due to selective clonal growth in the PDXs that allows detection of these low allelic frequency mutations. The results provide the strongest evidence yet that PDXs established from lung cancers closely mimic the characteristics of patient primary tumors. Abstract : What's new? Non‐small cell lung cancers (NSCLCs) are histologically and genetically diverse, with only a small fraction of patients exhibiting common cancer‐driving mutations. While translating that diversity into clinically relevant models has proven difficult, the present study suggests that at least some long‐standing challenges may be overcome with patient‐derived tumor xenografts (PDXs). PDXs were established by implanting and growing surgically resected human tumor tissue into mice. Subsequent genomic and proteomic profiling revealed fidelity between PDXs and the molecular pathology of matched patient tissues for a subset of models. Compared with cell lines, PDXs more completely recapitulated lung cancer pathogenesis in patients.